Where do women give birth in rural Tanzania? - Kruger, C.; Olsen, O.; Mighay, E.; Ali, Mohammed (Rural and Remote Health, 2011)
Introduction: Skilled birth attendance is one of the key factors in improving maternal and neonatal health but coverage is frequently less than 50% in many African and Asian countries, especially in rural areas. This article reports the findings on skilled birth attendance in a remote area with a large nomadic population in northern Tanzania. Methods: In a secondary analysis of data from a retrospective study on immunisation rates, data were compiled on the rates of skilled birth attendance at 8 mobile reproductive and child health clinics run by a rural first-referral hospital in the Mbulu area, covering the years 1998, 1999, 2006 and 2007. These data were analysed according to tribal affiliation and distance from health institutions with obstetric services.Results: Based on 3851 data sets, average rates of skilled birth attendance were 27%, 24%, 28% and 30% in 1998, 1999, 2006 and 2007, respectively (p = 0.02). At individual clinics, rates could be as low as 5?10%. Only at one clinic, significant improvement occurred over time (p < 0.01). In the univariate analysis, affiliation to the Iraqw tribe was a strong predictor of higher rates ofskilled birth attendance in comparison with the nomadic Datoga tribe for all years combined (odds ratio [OR] 2.43 [95% confidence interval CI 1.92-3.07]), whereas distance showed only a minor influence (OR 1.02 [95% CI 1.01-1.02]). In the multivariate analysis, only tribal affiliation in 2007 (OR 2.69 [95% CI 1.12-6.46]) and for all years combined (OR 1.65 [95% CI1.04-2.61]) was a significant factor.Conclusions: This study documented lower than the national average rates of skilled birth attendance in a rural area in Tanzania, especially among the nomadic Datoga tribe, over several years. The effect of distance was not consistent. To increase rates of women giving birth with skilled attendance in rural, remote settings and in populations with large proportions of nomadic people, a multi-facetted approach involving education in and sensitisation for pregnancy- and delivery-related issues, support for plannedand emergency transportation, and improved quality of obstetric and neonatal services needs to be explored.